Investigation on Rutting Resistance of Asphalt Mixture Containing Crumb Rubber - Bin Abdul Hisam, Muhammad Nur Syafiq; Buhari, Rosnawati (Recent Trends in Civil Engineering and Built Environment, 2023)
Crumb rubber is one of the modified materials included as additive in asphalt mix to improve the pavement quality on existing road structures. This raw material is made from recycled waste tires and undergoes several processes of impurity removal before being cut to a specified size. The purposes of this study were to identify the Optimum Bitumen Content (OBC) for rubberised asphalt mixture and evaluate the rutting resistance of rubberised asphalt mixture. This study has decided that the crumb rubber size should pass 0.425 mm and 0.150 mm of sieve size with 1, 2 and 3 % of the rubber content will be added into the mixture. Preparation for all testing samples were complied with Marshall mix design. The percentage of OBC applied into sample performance test was 5.5% as fulfilling the requirement in JKR standard. The rutting resistance of control mixture was the greatest while sample with 1% crumb rubber content had the nearest results to control mixture compared to 2% and 3% crumb rubber. All samples including with crumb rubber content had passed the parameters of rutting resistance which are dynamic modulus and creep steady slope as specified in JKR standard.